Synthesis and characterization of TiO sub(2)-pillared Romanian clay and their application for azoic dyes photodegradation - Dvininov, E; Popovici, E; Pode, R; Cocheci, L; Barvinschi, P; Nica, V (Journal of hazardous materials, 2009)
The synthesis and properties of metal oxide pillared cationic clays (PILCs) has been subject to numerous studies in the last decades. In order to obtain TiO sub(2)-pillared type materials, sodium montmorillonite from Romania-areal of Valea Chioarului, having the following composition (% wt): SiO sub(2)-72.87; Al sub(2)O sub(3)-14.5; MgO-2.15; Fe sub(2)O sub(3)-1.13; Na sub(2)O-0.60; K sub(2)O-0.60; CaO-0.90; PC-5.70 and cation exchange capacity, determined by ammonium acetate method, of 82meq/100g, as matrix, was used. Sodium form of the clay was modified, primarily, by intercalation of cetyl-trimethylammonium cations between negatively charged layers which will lead to the expantion of the interlayer space. For the preparation of the TiO sub(2)-pillared clay, the alkoxide molecules, as titania precursor, were adsorbed onto/into clay samples (1mmol Ti/g clay), in hydrochloric acid environment, the resulted species being converted into TiO sub(2) pillars by calcination. The as-prepared materials have been used as catalysts for Congo Red dye photodegradation, under UV. The photocatalytic activity of the pillared clays is a function of TiO sub(2) pillars size, their increase leading to the enhancement of the contact areas between dye solution and photoactive species present in the interlayer space. The structural characteristics and properties of the obtained materials were investigated by X-ray Diffraction, Thermogravimetry Analysis, UV-vis Diffuse Reflectance, Transmission Electron Microscopy and Energy Dispersive X-ray Analysis.